2006
DOI: 10.1021/je060263u
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Total Reduced Sulfurs (Hydrogen Sulfide, Methyl Mercaptan, Dimethyl Sulfide, and Dimethyl Disulfide) in Liquids

Abstract: The solubility of the total reduced sulfurs, which include hydrogen sulfide (H2S), methyl mercaptan (methanethiol, CH3SH), dimethyl sulfide (CH3SCH3), and dimethyl disulfide (CH3S2CH3), is of great interest in various applications in the chemical, oil, and gas industries and in environmental protection as well. They can occur naturally in the environment and can also be present in numerous industrial gaseous streams (petroleum, natural gas, some chemical industries like the pulp and paper industry). The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 125 publications
0
20
0
Order By: Relevance
“…A data compilation is also available on the web for pure water (http://webbook.nist.gov/). For DMS and DMDS solubility in water, Iliuta and Larachi [7] provided an extensive review. According to these authors, the solubility data are quite scarce, while the experimental temperatures used differ greatly and cover a wide range.…”
Section: Chemical Productsmentioning
confidence: 99%
“…A data compilation is also available on the web for pure water (http://webbook.nist.gov/). For DMS and DMDS solubility in water, Iliuta and Larachi [7] provided an extensive review. According to these authors, the solubility data are quite scarce, while the experimental temperatures used differ greatly and cover a wide range.…”
Section: Chemical Productsmentioning
confidence: 99%
“…The Henry's coefficient can be found in the literature, using the compilation of Sander or specific articles [36][37][38][39][40][41]. When the value cannot be found for a specific compound or in specific conditions, it remains possible to use some thermodynamic models which provide good accuracies [39,[42][43][44][45].…”
Section: Mass Transfer Ratementioning
confidence: 99%
“…Due to their partial solubility at lower pHs, the chemical removal of fetid sulfur-containing compounds requires large amounts of sodium hydroxide and water (Iliuta and Larachi 2007). Several studies have reported that, during bio-filtration methods, odorous contaminants are adsorbed from the air into the water present in the organic bed [i.e., bioactive layer (biofilm)] where they can be aerobically degraded to various end-products or incorporated into biomass (McNevin and Barford 2000).…”
Section: Introductionmentioning
confidence: 99%